2017
DOI: 10.3311/ppso.9758
|View full text |Cite
|
Sign up to set email alerts
|

Are Managers in Slovakia Ethical Leaders? Key Findings on the Level of Ethical Leadership in the Slovak Business Environment

Abstract: Ethical leadership is a highly relevant and up-to-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…While the regional differences in VOL between Bratislava region and the other Slovak regions were proved, the difference between Slovak and foreign-owned companies was not confirmed. This is in sharp contrast with the prior ethical leadership research, where authors inferred that despite substantial economic differences no significant disparities in ethical leadership between Slovak regions were found and that the foreign-owned companies exhibited substantially higher levels of ethical leadership than the Slovak-owned companies (Lašáková et al 2017). Yet, here the VOL results are derived from a pilot study on a smaller number of participants and as such have to be confirmed in larger samples.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…While the regional differences in VOL between Bratislava region and the other Slovak regions were proved, the difference between Slovak and foreign-owned companies was not confirmed. This is in sharp contrast with the prior ethical leadership research, where authors inferred that despite substantial economic differences no significant disparities in ethical leadership between Slovak regions were found and that the foreign-owned companies exhibited substantially higher levels of ethical leadership than the Slovak-owned companies (Lašáková et al 2017). Yet, here the VOL results are derived from a pilot study on a smaller number of participants and as such have to be confirmed in larger samples.…”
Section: Discussioncontrasting
confidence: 84%
“…This is in line with results of a prior leadership research in Slovakia on a sample of more than 800 managers. It was carried out based on the ELS tool (Brown et al 2005) and showed that Slovak followers perceived their supervisors as ethical leaders on a slightly above average level with the mean value 5.07 measured on a seven-point scale (Lašáková et al 2017). Although here the results of VOLQ with the mean value of 4.67 are less in favour of the leaders, it should be noted that the sample in the prior research based on ELS included only managerial personnel, whereas in this study also non-managerial respondents have participated, who could have a more critical stance to their supervisors.…”
Section: Discussionmentioning
confidence: 99%
“…Their quality determines the existence of an enterprise, its prosperity, sustainable, and dynamic progress. Prosperous enterprises are aware of the fact that employees are the major contributors to profit, providing the chance for an enterprise to achieve the goals [97][98][99][100]. Human resources are a motive power affecting the success and sustainability of an enterprise [101].…”
Section: Discussionmentioning
confidence: 99%
“…The level of focus of organizations on education and development in Europe, as well as in the world, is a topic on which research networks are focused, such as the Cranfield Network (worldwide), HPDCEEUS (Human Potential Development in Central and Eastern European States) (Central and Eastern Europe), and PAS (Business Alliance of Slovakia) (in the Slovak Republic). What confirms the topicality of the issue and also promotes the whole community awareness of the need for change from random, unplanned access to education (i.e., education where necessary courses and training are carried out only on the basis of the need to acquire the given knowledge or experience) to a holistic approach to education, to the so-called concept of a learning organization of P.M. Senge [11,54], who characterizes the learning organization as a place where people continually expand their capacity to create the results they truly desire, where new and expansive patterns of thinking are nurtured, where collective aspiration is set free, and where people are continually learning to see the whole together [55].…”
Section: Internal System Of Employee Education and Development In Orgmentioning
confidence: 89%